Cytokines as prognostic biomarkers in pulmonary arterial hypertension. Issue 3 (23rd March 2023) - Boucly, Athénaïs; Tu, Ly; Guignabert, Christophe; Rhodes, Christopher; De Groote, Pascal; Prévot, Grégoire; Bergot, Emmanuel; Bourdin, Arnaud; Beurnier, Antoine; Roche, Anne; Jevnikar, Mitja; Jaïs, Xavier; et al.
Background: Risk stratification and assessment of disease progression in patients with pulmonary arterial hypertension (PAH) are challenged by the lack of accurate disease-specific and prognostic biomarkers. To date, brain natriuretic peptide (BNP) and/or its N-terminal fragment (NT-proBNP) are the only markers for right ventricular dysfunction used in clinical practice, in association with echocardiographic and invasive haemodynamic variables to predict outcome in patients with PAH. Methods: This study was designed to identify an easily measurable biomarker panel in the serum of 80 well-phenotyped PAH patients with idiopathic, heritable or drug-induced PAH at baseline and at first follow-up. The prognostic value of identified cytokines of interest was secondly analysed in an external validation cohort of 125 PAH patients. Results: Among the 20 biomarkers studied with the multiplex Ella platform, we identified a three-biomarker panel composed of β-NGF, CXCL9 and TRAIL that were independently associated with prognosis both at the time of PAH diagnosis and at the first follow-up after initiation of PAH therapy. β-NGF and CXCL9 were predictors of death or transplantation, whereas high levels of TRAIL were associated with a better prognosis. Furthermore, the prognostic value of the three cytokines was more powerful for predicting survival than usual non-invasive variables (New York Heart Association Functional Class, 6-min walk distance and BNP/NT-proBNP). The results were validated in a fully independent external validation cohort. Conclusion: The monitoring of β-NGF, CXCL9 and TRAIL levels in serum should be considered in the management and treatment of patients with PAH to objectively guide therapeutic options. β-NGF, CXCL9 and TRAIL are independently associated with PAH prognosis at baseline and at follow-up. Prognostic value of the 3 cytokines is more powerful for predicting transplant-free survival than usual non-invasive variables (NYHA FC, 6MWD and BNP). http://bit.ly/3gnF0Vb